Tool Development for Human Audible Spectrum Compensation - Filomena Soares, Francisco Gonçalves; Carvalho, Vítor; Machado, José (Recent Innovations in Mechatronics, 2015)
Communication relies on good understanding. Humans relate to each other through visual, audible and tactile communication. It is imperative that the audible communication message reaches the receiver in good conditions, in order to keep a healthy, smooth and understandable speech. There are some disturbances in human speech and communication when hearing damage is present. Nowadays, hearing loss is a frequent injury, caused by noise pollution, daily stress or noisy workplaces. Yet, it can be treated by several ways. This project consists in developing a tool that captures the emitter's voice audible spectrum, filters the noise and other frequencies, and compensates the message, enabling the listener/receiver understanding. The purpose of this research is not aimed to substitute nor compete with hearing aids in the market, which are well-developed, certified and prescribed by Otorhinolaryngology clinicians. The focus of this study is to identify the issues of human hearing loss and to develop an algorithm for hearing compensation by using filtering techniques in a simulated environment applied to a hearing model.